95.2k views
5 votes
Multiply.

(7a-1)(x^2+2x-5)

User Nikhilweee
by
5.0k points

2 Answers

2 votes

Answer:

7ax2+14ax−x2−35a−2x+5

Explanation:

(7a+−1)(x2+2x+−5)

=(7a)(x2)+(7a)(2x)+(7a)(−5)+(−1)(x2)+(−1)(2x)+(−1)(−5)

=7ax2+14ax−35a−x2−2x+5

=7ax2+14ax−x2−35a−2x+5

User Tom Maton
by
4.9k points
3 votes

Answer:

Explanation:

(7a - 1) (x² +2x -5) =7a*((x² +2x -5) + (-1)*(x² +2x -5)

= 7a*x² + 7a*2x + 7*(-5) +(-1)*x² +(-1)*2x + -5*-1

= 7ax² + 14ax - 35 - x² -2x + 5

= 7ax² - x² + 14ax - 2x -30

User Oleg Tarasov
by
4.9k points